Music Studio in Malang - Ubaidillah, S; Wulandari, D (KnE Social Sciences, 2018)
The study aims to know how social capital (trust, reciprocity, network) and implication on music studio that has influence in normal price, duration, and the choice of specification of the lease and recording on music studio in Malang. This study uses qualitative method by using indepth interview, observation, and documentation techniques. Based on the study, it is described that social capital component such as trust, reciprocity, and network have effect on less price, less duration, and the choice of specification of the lease. Music studios in Malang that apply the social capital in the transaction with customer will get more information about market and promotion from customer without cost. Keywords: Social Capital, Trust, Reciprocity, Network, Music Studio